Ankle arthrodesis through Meary’s anterolateral access - Pansini, José Vicente; Baggio Pereira, Cesar Augusto; Batista , Flamarion dos Santos; Sabião, Kauê; Hiraga, Cássio (Journal of the Foot & Ankle, 2021)
Objective: This study aimed to assess indications for surgical treatment, position of the ankle, time and rate of fusion after arthrodesis; to ascertain whether the technique provides fusion rates similar to those described in the published literature; and to quantify patients’ improvement according to the AOFA and VAS scores, and patients’ satisfaction using a Likert scale. Methods: This is a clinical study with a cohort of 18 patients (9 women and 9 men) with a mean age of 49.10 years, conducted from 2006 and 2016. Results: Post-traumatic arthrosis (88.88%), rheumatoid arthritis (5.56%), and Charcot-Marie-Tooth disease (5.56%) motivated the surgeries. Six ankles fused in an equinus position, and 12 of them in a neutral position. Five ankles fused in valgus angulation, and 13 in a neutral position. Five ankles fused in external rotation, 2 in internal rotation and 11 in a neutral position. In the postoperative period, American Orthopaedic Foot and Ankle Society (AOFAS) and visual analogue scale (VAS) scores showed an improvement of 31.6 points and 5.1 points, respectively. Regarding the Likert scale, 2 patients reported being very satisfied, 14 satisfied, and 2 partially satisfied. Conclusion: Fusion in a 100% of cases and patients’ overall satisfaction have led to the conclusion that this treatment method is appropriate to attain ankle fusion, with results similar to those found in the medical literature. Level of Evidence IV; Therapeutic Studies; Case Series.